2010
DOI: 10.1590/s0066-782x2010005000094
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome metabólica e menopausa: estudo transversal em ambulatório de ginecologia

Abstract: Background: In Brazil, there are few studies of the metabolic syndrome in the general population, and even fewer studies that establish a correlation between metabolic syndrome and climacteric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
24
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 34 publications
11
24
2
4
Order By: Relevance
“…Cross-sectional population-based studies showed prevalence similar to that found in our study-56.9% (among women over 45 years) in the semi-arid region of Bahia [25] and 59.9% (in women over 60 years) in Novo Hamburgo, state of Rio Grande do Sul [26]. However, Figueiredo Neto [8], investigating women in climacteric period in a gynecology clinic in Maranhão, found lower prevalence, of 34.7% [8]. This study, like ours, was performed in public health service, with the average age of women of 49.7 years, slightly lower than ours.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Cross-sectional population-based studies showed prevalence similar to that found in our study-56.9% (among women over 45 years) in the semi-arid region of Bahia [25] and 59.9% (in women over 60 years) in Novo Hamburgo, state of Rio Grande do Sul [26]. However, Figueiredo Neto [8], investigating women in climacteric period in a gynecology clinic in Maranhão, found lower prevalence, of 34.7% [8]. This study, like ours, was performed in public health service, with the average age of women of 49.7 years, slightly lower than ours.…”
Section: Discussionsupporting
confidence: 86%
“…In another study, the prevalence of MetS was 29.8% and an increase in prevalence as the age increases was noticed [7]. In a study by Figueiredo Neto [8], women between 40 and 45 years had a prevalence of MetS of 14.1%, while for women between 56 and 64 years the prevalence was 66.7%. In this study, the increase in the prevalence of MetS in post-menopausal women was caused mainly by the increase of age.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, the climacteric coincides with the onset and aggravation of risk factors for the development of Metabolic Syndrome [11], with diabetes one of the most prevalent components of this syndrome [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, especially in the north and northeast, studies that draw associations between components of the metabolic syndrome, such as diabetes and menopause, are extremely scarce [12].…”
Section: Introductionmentioning
confidence: 99%